PENGARUH STRATEGI PROMOSI GRATIS ONGKOS KIRIM, DISKON, DAN CASHBACK SHOPEE TERHADAP KEPUTUSAN PEMBELIAN GEN Z DI ERA DIGITAL MARKETING (studi kasus pada gen z di kecamatan karanggeneng) - Hasmah, Hasmah; Irawan, Mohamad Rizal Nur; Sundari, Ariefah (J-EEMB (Journal of Economic Entrepreneurship and Management Business), 2025)
The advancement of digital technology has significantly influenced consumer behavior, especially in online shopping. Generation Z, born between 1997 and 2012, is a generation highly familiar with digital platforms and actively uses e-commerce services such as Shopee. This study aims to examine the effect of Shopee’s promotional strategies—free shipping, discounts, and cashback—on the purchasing decisions of Gen Z in Karanggeneng District, Lamongan. This research uses a quantitative approach with an associative method. Data were collected through questionnaires distributed to 100 Gen Z respondents who had made at least two purchases on Shopee within the last six months. The sampling technique used was purposive sampling. Data analysis was performed using multiple linear regression with the help of SPSS software. The findings from Chapter IV reveal that the variables of free shipping, discount, and cashback each have a positive and significant effect on purchasing decisions both partially and simultaneously. Among these, free shipping has the most dominant influence on Gen Z’s decision-making process. The R² value of 0.625 indicates that 62.5% of the variation in purchasing decisions can be explained by the three promotional variables studied. The remaining 37.5% is influenced by other factors not examined in this study. Additionally, the F-test confirms that the three promotional strategies together significantly affect purchasing decisions. These results confirm that promotional features such as free shipping, discounts, and cashback are effective tools for influencing purchasing behavior among Gen Z. This research contributes to the understanding of digital marketing effectiveness and offers insights for e-commerce businesses in tailoring promotional strategies to young consumers.